Morphological traits related to potential invasiveness of two subspecies of the crayfish Faxonius neglectus. (11th July 2022) - Magoulick, Daniel D.; Wynne, K. Carter; Clark, Jessica
Abstract: Biological invasions have major environmental and economic impacts, and pose a serious threat to global biodiversity. Invasive crayfish species are one of the greatest threats to native crayfish biodiversity. Additionally, almost 50% of US and Canadian species are considered at risk, making crayfish one of the most imperiled taxonomic groups in the world. Small‐scale (extralimital) invasions are often overlooked and may be more common than large‐scale (extraregional) invasions. One example of an extraregional and extralimital invader is the Ringed Crayfish ( Faxonius neglectus ), which has been independently introduced multiple times to drainages throughout the United States, including those adjacent to its native range. Traits related to invasiveness, such as chelae size, are suggested to differ between invasive crayfish from extralimital and extraregional source populations with larger size related to increased invasiveness. We examined morphological traits related to invasion potential for both subspecies of F . neglectus, F . neglectus neglectus and F . neglectus chaenodactylus . We sampled 28 stream sites within the known native range of F . neglectus, including the Neosho and Upper White River drainages in Oklahoma, Arkansas and Missouri. Total carapace length, chelae length and chelae width of 30 adult male F . neglectus were measured from each site. We found significant differences in crayfish morphological characteristics among stream sites. We found significantly greater chelae length:carapace length (ChL:CarL) and chelae width:chelae length (ChW:ChL) in F . neglectus chaenodactylus than F . neglectus neglectus . Even among F . neglectus neglectus populations, there were significant differences in ChL:CarL and ChW:ChL. Morphological characteristics suggest that F . neglectus chaenodactylus and some populations of F . neglectus neglectus may be pre‐adapted to the role of invader.